Trains, Trade and Transaction Costs: How does Domestic Trade by Rail affect Market Prices of Malawi Agricultural Commodities? - Wouter Zant (Tinbergen Institute, 2015)
We measure the impact of low cost transport by rail in Malawi on the dispersion of agricultural commodities prices across markets, by exploiting the quasi experimental design of the nearly total collapse of domestic trade by rail in January 2003, due to the destruction of a railway bridge at Rivirivi, Balaka. Market pairs connected by rail when the railway line was operational, are intervention observations. Estimations are based on monthly market prices of four agricultural commodities (maize, groundnuts, rice and beans), in 27 local markets, for the period 1998-2006. Railway transport services explain a 11% to 18% reduction in price dispersion across markets. Geographical reach of trade varies by crop, most likely related to storability and geographical spread of production. Perishability appears to increase impact reflecting the lack of intertemporal arbitrage. Overall, impacts are, however, remarkably similar in size across commodities.
Keywords: F14; N77; O13; O18; O55; Q13; 330; trade; crop prices; transaction costs; rail infrastructure; Malawi; sub Saharan Africa